Electrocatalytic fixation of N2 into NO3−: electron transfer between oxygen vacancies and loaded Au in Nb2O5−x nanobelts to promote ambient nitrogen oxidation. Issue 32 (6th August 2021) - Zhang, Yintong; Du, Feng; Wang, Ruyi; Ling, Xintong; Wang, Xiaoyong; Shen, Qing; Xiong, Yujie; Li, Tao; Zhou, Yong; Zou, Zhigang
Abstract : The electron transfer from Au to oxygen vacancies in Au-Nb2 O5− x hybrid electrocatalyst modifies the electronic structure of active sites near the interface, which enhances the performance of NOR and suppresses the activity of competitive OER. Abstract : The electrocatalytic nitrogen oxidation reaction (NOR) is a promising alternative to the industrial synthesis of nitrate. However, with the enhancement of NOR activity by modification methods, the competitive oxygen evolution reaction (OER) is always improved simultaneously. Here, a hybrid electrocatalyst composed of Au nanoparticles and oxygen vacancy-enriched niobium oxide nanobelts (Au–Nb2 O5− x ) was prepared on niobium foil for N2 fixation into NO3 − . The results of X-ray photoelectron spectroscopy (XPS) and electron paramagnetic resonance (EPR) demonstrate that electron transfer occurs between Au nanoparticles and the oxygen vacancies in Nb2 O5− x nanobelts, which adjusts the electronic structures of oxygen vacancies near the Au/Nb2 O5− x interface. Electrochemical and N2 temperature-programmed desorption (TPD) tests indicate that the optimization of the electronic structure suppresses the activity of the competitive OER on oxygen vacancy sites and facilitates nitrogen adsorption on the surface of Au–Nb2 O5− x, which significantly enhances the NOR performance of the electrocatalyst.